2021
DOI: 10.1021/acs.jchemed.0c01479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Concurrent Enrollment Preparatory Course on Student Achievement and Persistence in General Chemistry

Abstract: A concurrent preparatory course was developed for a university-level general chemistry course to replace prerequisite classes and online exercises implemented in previous years. The concurrent preparatory course was structured with 3 h of active learning class time. Lecture content was delivered asynchronously online. Topics were chosen on the basis of fundamental topics needed to succeed in general chemistry. Topics included both those typically found in a preparatory chemistry class as well as some simpler t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
(65 reference statements)
0
6
1
Order By: Relevance
“…It is important to note some recent studies that showed the positive synergistic effects of concurrent enrollment of a preparatory course with regular general chemistry. The reported work included implementing a preparation course concurrently with the traditional chemistry course to replace the prerequisite for general chemistry, 56 using concurrent programs for first-year students. 57 Indeed, a proper transition from the summer academy to the regular academic year and continued student support will benefit students for continued success.…”
Section: ■ Final Remarksmentioning
confidence: 99%
“…It is important to note some recent studies that showed the positive synergistic effects of concurrent enrollment of a preparatory course with regular general chemistry. The reported work included implementing a preparation course concurrently with the traditional chemistry course to replace the prerequisite for general chemistry, 56 using concurrent programs for first-year students. 57 Indeed, a proper transition from the summer academy to the regular academic year and continued student support will benefit students for continued success.…”
Section: ■ Final Remarksmentioning
confidence: 99%
“…successful approaches have included a preparatory course that runs concurrently with the main chemistry teaching. 12 Herein we describe a new compulsory "Introduction to University Chemistry" module at Cardiff University, designed to assist all students with the transition to university.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Voluntary introductory modules that bridge the gap from school to university have been introduced at other chemistry departments, where students who attended performed significantly better than students who did not . Other successful approaches have included a preparatory course that runs concurrently with the main chemistry teaching …”
Section: Introductionmentioning
confidence: 99%
“…Research at our own university has shown these results apply to our student population. 38−40 In our prior publication, 41 we discussed the implementation and design of a concurrent enrollment preparatory course in general chemistry. Offering a full concurrent enrollment course provided the benefits of supplemental instruction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Performance improvements on the common final exam, as well as improvements in the one-year retention, were observed. 41 Deciding who should be placed into preparatory chemistry classes has various difficult aspects. 42,43 Though many placement testing methods have been developed, 44−46 they are costly and largely ineffective.…”
Section: ■ Introductionmentioning
confidence: 99%